Piquiá Shells (Caryocar villosum): a fruit by-product with antioxidant and antiaging properties in caenorhabditis elegans - Roxo, Mariana; Peixoto, Herbenya; Link, Pille; Lima, Emerson; Wink, Michael (Oxidative medicine and cellular longevity, 2020)
In a context of rising demand for sustainable antiaging interventions, fruit processing by-products are a promising source of bioactive compounds for the production of antiaging dietary supplements. Piquiá (Caryocar villosum) is a native Amazonian fruit consisting of 65% nonedible shells. In the present study, the phytochemical profile of a hydroalcoholic extract of piquiá shells (CV) was characterized by LC-MS/MS analysis. Its antioxidant and antiaging activities were investigated using the nematode Caenorhabditis elegans as an in vivo model. CV is mainly composed by hydrolysable tannins and triterpenoid saponins. The extract enhanced stress resistance of wild-type and mutant worms by reducing the intracellular levels of reactive oxygen species (ROS) and by increasing their survival against a lethal dose of the prooxidant juglone. These effects involved the upregulation of sod-3 and downregulation of gst-4 and hsp-16.2, studied through the GFP fluorescent reporter intensity and at the transcriptional level by qRT-PCR analysis. CV extended the lifespan of wild-type worms in a DAF-16/FoxO- and SKN-1/Nrf-dependent manner. Taken together, our findings indicate piquiá shells as potential candidates for nutraceutical applications. Further studies are needed to validate the relevance of our findings to antiaging interventions in humans.
Gesehen am 14.10.2020